Value-added asparagus (Asparagus officinalis L.) as healthy snacks using vacuum frying - Maisont, Suchada; Samutsri, Wisutthana; Khamweera, Pemika; Phae-ngam, Wuttichai; Limsuwan, Pichet (Frontiers in Sustainable Food Systems, 2023)
This study investigated the possibility of using asparagus (Asparagus officinalis L.) to produce healthy snacks using vacuum frying. The tip and middle part of asparagus Grade C were soaked in 0.1% Calcium chloride solution and blanched at 95–98°C for 45 s, immediately soaked in water at 30°C for 2 min and packed in the bags to freeze at −18°C before vacuum frying. The samples were fried at 80°C and 986 mbar for 38, 40 and 42 min, and then excess oil in the sample was removed by a centrifuge before being measured properties. The effects of different frying times on the physicochemical and sensory characteristics of the vacuum-fried asparagus were analysed. A scanning electron microscope was used to study the structure of the vacuum-fried product. The result reveals that increasing frying time decreased moisture content, aw, yield, greenness value and crispiness of vacuumed snacks but increased lightness and yellowness values. SEM showed that vacuumed snacks with increasing frying time resulted in a gradual increase in the size of pores inside the product. When the frying time increased to 42 min, collapsed pores were observed, indicating a breakdown structure. A sensory evaluation of seasonings on vacuum-fried asparagus found that fried asparagus with truffle seasoning had the highest preference levels for all sensory attributes. The truffle seasoned fried asparagus at 80°C under vacuum at a pressure of 986 mbar for 40 min contained protein and fibre content of 14.21 and 15.55%, respectively, vitamin A and beta-carotene of 2.717 μg and 16.30 μg, respectively, and calcium and iron of 182.68 mg and 2.88 mg, respectively. Microorganisms found are under the regulated amount according to the Notification of the Ministry of Public Health. This study demonstrates that asparagus Grade C can be used to produce healthy and acceptable fried snacks.